Investigating Tau Pathology in the Retina and Anterior Segment Structures of the Eye in a 3-Nitropropionic Acid–Induced Tauopathy Mouse Model - Qasem, Mohamed Sayed Ahmed Abdel-Kader (AUC Knowledge Fountain, 2026)
Background and Objectives: Alzheimer's disease, the most prevalent neurodegenerative disorder in older adults, is characterized by accumulation of hyperphosphorylated tau and amyloid-beta (Aβ) plaques in the central nervous system. Given the retina's shared embryological origin with the brain, its direct neural connectivity via the optic nerve, and similarities in vasculature and age-related degeneration patterns, retinal pathology may serve as an early, non-invasive biomarker for Alzheimer's disease. This study employed 3-nitropropionic acid (3NP) as a pathway-specific tauopathy model driven by mitochondrial dysfunction. The study particularly aimed to investigate whether retinal and corneal tau pathology reflects underlying tau-related neurodegeneration triggered by mitochondrial complex II inhibition using 3NP in mice. Methods: Adult male Swiss Webster mice, aged 2 months old, were treated with 3-nitropropionic acid (3NP, 15 mg/kg, every other day for one month), a suicide inhibitor of mitochondrial complex II that induces tau hyperphosphorylation. Animals were divided into three groups: untreated controls, 3NP-treated animals sacrificed at one month (Group A, 4-month age), and three months (Group B, 6-month age) post-injection. Comprehensive neurobehavioral assessments evaluated anxiety-like behaviors (open field test, light-dark transition box), cognitive function (novel object recognition test), and depression-like phenotypes (forced swim test). Immunohistochemical analysis characterized tau pathology using phospho-tau specific epitopes (AT8, AT100), neuronal integrity markers (β-tubulin III), and signaling pathway dysregulation (CDK5, phospho-AMPK) in retinal and corneal tissues. Statistical analyses were conducted via ANOVA with post-hoc Tukey tests. Results: 3NP-treated mice exhibited progressive behavioral impairments. Behavioral analysis revealed progressive neurodegeneration characterized by increased anxiety-like behaviors, significant impairment in recognition memory (44% reduction in recognition index), and depression-like phenotypes at 6 months. Immunohistochemical findings demonstrated a temporal progression of tau pathology: early tau hyperphosphorylation (AT8+) at 4 months preceded aggregation (AT100+) at 6 months. β-Tubulin III expression progressively declined, indicating retinal ganglion cell loss, particularly in the ganglion cell layer and inner plexiform layer. CDK5 and phospho-AMPK demonstrated pathological hyperactivation, reflecting mitochondrial dysfunction-induced metabolic crisis and tau kinase dysregulation. Critically, tau pathology extended beyond the retina to peripheral corneal structures, including sensory nerve fibers and supporting cell layers, with similar temporal progression of phosphorylation and aggregation cascades. Conclusions: This study establishes that 3NP-induced mitochondrial dysfunction successfully recapitulates core features of tauopathy and neurodegeneration that manifest in both central (retinal) and peripheral (corneal) neural tissues. Although amyloid pathology and genetic susceptibility are not represented, 3NP-induced model effectively mimics tau hyperphosphorylation, aggregation, and neurodegenerative processes central to Alzheimer’s disease mechanisms. The parallel progression of behavioral deficits, retinal neurodegeneration, and corneal pathology supports the retina and cornea as accessible windows for monitoring Alzheimer's disease-related pathology. These findings have significant future implications for early diagnosis through non-invasive ophthalmic examination [e.g., optical coherence tomography (OCT) and electroretinography (ERG)] and highlight the potential of retinal and corneal biomarkers for tracking therapeutic efficacy in tauopathy-targeted interventions.